Rural carers online: A feasibility study - Dow, B.; Moore, K.; Scott, P.; Ratnayeke, A.; Wise, K.; Sims, J.; Hill, Keith (Wiley-Blackwell Publishing Asia, 2008)
Objective: To test the feasibility (for a potential randomised controlled trial) of a computer intervention for improving social interaction and promoting the mental health of rural carers. Design: The study combined pre- and post-intervention measures with interviews to determine the feasibility of the intervention and the acceptability of the study design to participants. The intervention consisted of providing 14 rural carers with computers and a 4-week training program on basic computer skills, using email and the Internet. Setting: The study was conducted in a rural community setting. Participants: The carers were 12 women and two men, aged from 50 to 81 years, with an average of 65.5 years. Main outcome measures: Measures of social isolation (UCLA Loneliness Scale), depression (Geriatric Depression Scale), carer burden (Zarit Burden Interview) and computer confidence were taken at baseline and at a 3-month follow-up. Interviews were completed at follow-up to discuss outcomes of the study. A focus group discussion was conducted with 11 participants to discuss the study and resolve computer issues. Results: Most carers reported increased confidence in email and Internet use. There was improvement for most participants in depressive symptoms and social isolation, but little change in carer burden. Participants identified many social benefits associated with the computer intervention, such as intergenerational connection, community building, skills and confidence and preparation for the future. Conclusion: The intervention was found to be practical and acceptable for a group of older carers. It was concluded that it would be feasible to conduct a large randomised controlled trial of the intervention. © Journal compilation © 2008 Blackwell Publishing.